Effect of adding the sifting Pomegranates seed meals to wheat flour on produced characteristics of biscuits - محمد , رامز (Latakia University Journal -Biological Sciences Series, 2022)
The data of Pomegranates fruits seeds analysis indicated that seeds contained low percentages of remained moisture at seeds, after fluid extraction and dreid it. Also the studied seeds, contained high percentages of oil and grude fiber which reached (50, 35%) respectively , as dry weight basis. While dried seeds contained lower amounts of total soluble sugars reached (3%). Finally, The data of Pomegranates fruits seeds analysis showed that seeds contained high percentages of poly phenol compounds reached (0.332%). Adding the sifting meals of the Pomegranates seeds to wheat flour mixtures caused increasing in folowing percentages of components: (moisture , fibers , ash , starch and total soluble sugars ). Also the (5 and 10%) percentages adding caused a slight reducing in gluten quality , while a reducing in gluten quality was at (15 , 20 and 25%) percentages. Also the adding of tested meals caused reducing the sensory properties of produced biscuits , except the sensory properties of (5 and 10%) percentages , which improved significantly , comparing with control sample. Finally , Rheological properties of the( 5 and 10%) blended flour , show increase in thermal stability of amylases comparing with control sample , while other characteristics did,not effected clearly.